A Logit Model of Homeownership - Li, Mingche M. (Econometrica, 1977)
[This paper estimates all possible multidimensional interaction effects in a logit model of homeownership, assesses the relative importance of these interactions, and interprets the results in light of existing theories of housing consumption.]